2019
DOI: 10.1186/s12884-019-2419-z
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of community-based mentor mothers to support HIV-positive pregnant women on antiretroviral treatment in western Kenya: a qualitative study

Abstract: Background Option B+ is a comprehensive antiretroviral treatment (ART) designed for HIV-infected pregnant/ postpartum women. However, barriers to implementing Option B+ and establishing long-term ART adherence while facilitating retention in prevention of mother to child transmission of HIV (PMTCT) services remain. Community-based mentor mothers (cMMs) who can provide home-based support for PMTCT services may address some of the barriers to successful adoption and retention in Option B+. Thus, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 43 publications
3
36
0
Order By: Relevance
“…Our findings suggest that future interventional studies to further increase partner disclosure among women in PMTCT care, such as counselling in support groups [48] or community interventions [49], should consider focusing on women ≥25 years and women diagnosed with HIV during the past 6 months. Therefore, continued counselling at routine follow-up visits could support and empower women in this effort, helping reduce concerns about isolation or lack of support from family and friends as well as concerns about conflict and separation from a partner.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Our findings suggest that future interventional studies to further increase partner disclosure among women in PMTCT care, such as counselling in support groups [48] or community interventions [49], should consider focusing on women ≥25 years and women diagnosed with HIV during the past 6 months. Therefore, continued counselling at routine follow-up visits could support and empower women in this effort, helping reduce concerns about isolation or lack of support from family and friends as well as concerns about conflict and separation from a partner.…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, continued counselling at routine follow-up visits could support and empower women in this effort, helping reduce concerns about isolation or lack of support from family and friends as well as concerns about conflict and separation from a partner. Counselling could, for example, involve peer-support [2,49] and discussing what to do in worstcase scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that peer‐centred approaches can effectively be combined with other interventions [72] and encourage other reproductive health behaviours [73]. These trial findings are largely supported by qualitative research, which confirm the overall feasibility and acceptability of the intervention [74‐76], including among adolescents [77]. For widespread implementation, however, adaptations may be required to fully optimize the role of peer supporters within the health system [78].…”
Section: Resultsmentioning
confidence: 71%
“…The research team followed a rigorous protocol to ensure the consistency and validity of coding during the qualitative analysis, although a formal inter-rater reliability statistic was not computed. We used an iterative process of discussions with co-authors and research team members to develop initial codes that were then reconciled into an agreed coding framework and subsequently applied to the data in the final analysis [ 31 , 32 , 33 ]. This approach has also been used in multiple studies of quality improvement in sub-Saharan Africa [ 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…We used an iterative process of discussions with co-authors and research team members to develop initial codes that were then reconciled into an agreed coding framework and subsequently applied to the data in the final analysis [ 31 , 32 , 33 ]. This approach has also been used in multiple studies of quality improvement in sub-Saharan Africa [ 32 , 33 ]. Coding was primarily conducted by two researchers, including one Malawian researcher, and the Malawi based research team (the principal investigator and site research staff) offered feedback via participation in debriefing sessions.…”
Section: Methodsmentioning
confidence: 99%